NECPAL tool prognostication in advanced chronic illness: a rapid review and expert consensus. Issue Volume 12(2022)Issue e1 (2nd April 2020) - Gómez-Batiste, Xavier; Turrillas, Pamela; Tebé, Cristian; Calsina-Berna, Agnès; Amblàs-Novellas, Jordi
Abstract : Objective: To develop a proposal for a 2-year mortality prognostic approach for patients with advanced chronic conditions based on the palliative care need (PCN) items of the NECesidades PALiativas (NECPAL) CCOMS-ICO V.3.1 2017 tool. Methods: A phase 1 study using three components based on the NECPAL items: (1) a rapid review of systematic reviews (SRs) on prognostic factors of mortality in patients with advanced chronic diseases and PCNs; (2) a clinician and statistician experts' consensus based on the Delphi technique on the selection of mortality prognostic factors; and (3) a panel meeting to discuss the findings of components (1) and (2). Results: Twenty SRs were included in a rapid review, and 50% were considered of moderate quality. Despite methodological issues, nutritional and functional decline, severe and refractory dyspnoea, multimorbidity, use of resources and specific disease indicators were found to be potentially prognostic variables for mortality across four clinical groups and end-of-life (EoL) trajectories: cancer, dementia and neurologic diseases, chronic organ failure and frailty. Experts' consensus added 'needs' identified by health professionals. However, clinicians were less able to discriminate which NECPAL items were more reliable for a 'general' model. A retrospective cohort study was designed to evaluate this proposal in phase 2. Conclusions: We identified several parameters with prognostic value and linked them to the tool's utility to timely identify PCNs of patients with advanced chronic conditions in all settings of care. Initial results show this is a clinical and feasible tool, that will help with clinical pragmatic decision-making and to define services.